Semiotics and Forms Of Ecranization in the “Red Sparrow” Novel by Jason Matthews to the “Red Sparrow” Movie by Francis Lawrence - Sudirman, Sudirman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This research discusses the study of semiotics in the film Red Sparrow and the form of the novel's ecranization of the film Red Sparrow. In this study, every film has semiotics and every ecranization or change of literary work such as a novel that turns into a film includes reduction, variation changes and additions which are like words in novel literature, that writing becomes a moving image in a film consisting of of the plot, characters and setting. The purpose of this study is to analyze the semiotics contained in the film and to compare the forms of ecranization in the film and the novel Red Sparrow. The research method used is descriptive qualitative method. The approach used is the library research approach. Data was collected by reading, watching, taking notes and analyzing documents from novels to films. The results of this study indicate that in the Red Sparrow film there are three semiotics used and in the study of ecranization from the novel to the Red Sparrow film there are changes, additions and subtractions in the film.